Compressibility effects on laminar-turbulent boundary layer transition. (1st January 2011) - Arnal, Daniel; Vermeersch, Olivier
This article gives an overview of the compressibility effects, free-stream Mach number and wall temperature effects, on boundary layer laminar-turbulent transition from incompressible flow to low supersonic Mach number (0 < M e < 2). Distinction will be made between 'natural' and 'bypass' transitions. For boundary layers developing on 'perfect smooth' surface in a low free-stream disturbance environment the 'natural' transition is induced by modal instabilities and can be predicted using the linear stability theory, in particular the e N method. When the intensity of external disturbances increases (rough surface or high free-stream disturbance), an early 'bypass' transition is triggered. This transition is due to the amplification of streaky structures in the laminar zone. This article shows how transient growth theory can be applied to predict the bypass transition induced by 3D roughness elements and how compressibility effects influence such a transition.